Cardiovascular Disease Risk Profile and Risk Prediction Among Unskilled Workers of a Tertiary Care Teaching Hospital - Sekar, Ganesh; Venugopal, Vinayagamoorthy; Santhanakrishnan, Iswarya (National Journal of Community Medicine, 2022)
Background: Cardiovascular disease is the single largest cause for mortality and morbidity in the world and also in India. The prevalence of CVD risk factors in India is steadily increasing moreover CVD in Indians has been shown to occur prematurely. The study was designed to estimate the 10-year cardiovascular risk using region specific WHO/ISH risk prediction chart among unskilled workers of a tertiary care teaching hospital and to determine factors associated with risk. Material and methods: It were a hospital based cross sectional study. Based on the calculated sample size, 250 eligible workers were selected by simple random sampling. Using structured questionnaire, life style related risk factors namely, average daily consumption of fruits and vegetables, physical activity, perceived stress, tobacco and alcohol use was collected. BMI and BP were measured using standard protocol and classified following standard guidelines. Bio-chemical parameters were also measured. Results: Among 250 workers 37.2% and 10% consumed daily minimal recommended level of vegetables and fruits respectively, 21.1% was current tobacco user, 17.2% was alcohol drinkers, 50.4% were obese, 18.8% had high blood pressure, 6% had elevated cholesterol levels. Among the workers 46.7 % had <10% risk, 5.3% had 10% to <20% risk and, 3.3% had 20% to <30% risk to develop CVD within future 10 years of lifetime. Drivers and current alcoholics were significantly associated with being in the high-risk group. Conclusion: Employer initiated regular work place health screening and services need to be aimed at the unskilled workers, especially for CVD targeting drivers and alcoholics.